1993
DOI: 10.1203/00006450-199306000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Neural Crest Ablation Versus Sham Surgical Effects in a Chick Embryo Model of Defective Cardiovascular Development

Abstract: ABSTRACT. In chick embryos, ablation of premigratory neural crest destined for the third, fourth, and sixth pharyngeal arches results in persistent truncus arteriosus and interrupted aortic arch. Studies of cardiogenesis in these embryos have shown decreased ejection fraction and ventricular dilation with normal cardiac output. The experimental embryos that survive to d 11 of incubation have a higher cardiac output than nonsurvivors at the same earlier stage of development. We hypothesize that this survival is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Our M‐mode measurements provided a fractional shortening of 58%. This is higher than in humans (30%), but is similar to that seen in chick embryos (69%) (Leatherbury et al, 1993). We also assessed contractility using the Tei index as described by Tei et al (1995).…”
Section: Discussionsupporting
confidence: 73%
“…Our M‐mode measurements provided a fractional shortening of 58%. This is higher than in humans (30%), but is similar to that seen in chick embryos (69%) (Leatherbury et al, 1993). We also assessed contractility using the Tei index as described by Tei et al (1995).…”
Section: Discussionsupporting
confidence: 73%
“…Kirby et al (1990) inferred that aortic arch anomalies, caused by the decrease in the cardiac neural crest, altered blood flow characteristics, leading to abnormal morphogenesis in the proximal outflow tract via an upstream hemodynamic effect. Hemodynamic measurements of the neural crest‐ablated chick embryos (Tomita et al, 1991; Leatherburry et al, 1991, 1993) or Splotch mice (Conway et al, 1997b) revealed changes in hemodynamic or electrophysiological parameters. However, a direct relation between such physiological changes and morphogenesis has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A surprising finding was that removal of CNCCs had an impact on early cardiac function (stage 14–16) 24–28 hr before the CNCCs derivatives begin to enter the outflow tract (stage 25 in chicken embryos) (Leatherbury et al, , 1991, ; Tomita et al, ; Farrell et al, ). Cardiac contractility was depressed with reduced shortening fraction and ejection fraction, at stage 18 (68–72 hr or 3 days of incubation).…”
Section: Neural Crest Cell Disturbances Lead To Abnormal Functionmentioning
confidence: 99%
“…A surprising finding was that removal of CNCCs had an impact on early cardiac function (stage 14-16) 24-28 hr before the CNCCs derivatives begin to enter the outflow tract (stage 25 in chicken embryos) (Leatherbury et al, 1990b(Leatherbury et al, , 1993Tomita et al, 1991;Farrell et al, 2001).…”
Section: Nccs Regulate Early As Well As Late Cardiac Functionmentioning
confidence: 99%